Production Flexibility, Stochastic Separation, Hedging, and Futures Prices - Kamara, Avraham (Review of Financial Studies, 1993)
[We study a dynamic model where uncertainty about interim output adjustments causes producers to face price, cost and output uncertainty. Stochastically separable production decisions are independent of the producer's risk preferences and expectations and are based on the prevailing futures price as a certain output price. Conditions under which futures contracts achieve stochastic separation are established. Optimal hedging and maturity structure of futures contracts, equilibrium futures prices, and the effects of futures trading on output are studied. The systematic risk premium depends on the product of the futures beta and the covariance of the market return with production revenues.]